2019
DOI: 10.1108/ijoes-01-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nurses’ job satisfaction through remuneration: can materialism be a threat?

Abstract: Purpose Materialism has been reported to be on the increase among health workers, a situation that can oppose the expected effect of remuneration on nurses’ satisfaction. The purpose of this study is to examine the effect of materialism on the remuneration–satisfaction relationship in an attempt to know if materialism is a negative behaviour that can counter efforts to increase nurses’ satisfaction through remuneration. Design/methodology/approach The quantitative (correlational) research technique was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…The study results in Table 2 demonstrated a significant positive relationship between talent management and work engagement (r =0.489, p < 0.001). Thus, the study hypothesis was accepted because considerable studies show that there is a significant contribution between talent management practice and employee work engagement (Anlesinya, Amponsah-Tawiah, & Dartey-Baah, 2019;Ariana et al, 2018;Asiamah, Mensah, & Azinga, 2019;Chien & Yick, 2016;Naz & Sharma, 2017). Consequently, there is a need to continue with effective talent management practices in public hospitals to advance work engagement levels amongst the nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The study results in Table 2 demonstrated a significant positive relationship between talent management and work engagement (r =0.489, p < 0.001). Thus, the study hypothesis was accepted because considerable studies show that there is a significant contribution between talent management practice and employee work engagement (Anlesinya, Amponsah-Tawiah, & Dartey-Baah, 2019;Ariana et al, 2018;Asiamah, Mensah, & Azinga, 2019;Chien & Yick, 2016;Naz & Sharma, 2017). Consequently, there is a need to continue with effective talent management practices in public hospitals to advance work engagement levels amongst the nurses.…”
Section: Discussionmentioning
confidence: 99%
“…When managers take care of the feelings of their subordinates they create an atmosphere of relatedness in them (Deci and Ryan, 2012). A high level of relatedness makes the employees ready for change management (Asiamah et al, 2019;Shin et al, 2012). A study conducted by Skaalvik and Skaalvik (2014) shows that self-perceived autonomy outcomes in job engagement, motivation and satisfaction.…”
Section: Literature Review 21 Self-determination Theorymentioning
confidence: 99%
“…The compensation package includes different components such as allowances, commissions, and additional benefits. These are provided to employees upon the successful completion of individual or group job tasks (Asiamah et al, 2019). Remuneration encompasses the employee's basic salary, as well as additional elements such as bonuses and commissions, which are specified in the employment contract (Calvin, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%